MPPT of Magnus Wind System with DC Servo Drive for the Cylinders and Boost Converter. (18th August 2015) - Jinbo, Maro; Farret, Felix Alberto; Cardoso Junior, Ghendy; Senter, Daniel; Franklin Lorensetti, Marcelo
Abstract : This paper presents an algorithm MPPT (Maximum Power Point Tracking) for a Magnus wind system with a DC servo drive system (DC drive and BLDC motor) to rotate the turbine cylinders. The optimal cylinders rotation is the one to deliver the maximum power extracted from the wind tracked by fixed and adaptive step HCC (Hill Climbing Control) acting on the servo drive. The proposed wind system consists of a PMSG (Permanent Magnet Synchronous Generator), a three-phase diode rectifier, a DC/DC (boost) converter, and a resistive load. Furthermore, the boost converter acts with the fixed step HCC algorithm to track the maximum power operating point. Therefore, the MPPT for a Magnus wind system requires both tracking for the optimal cylinder speed and the optimal generator speed.